Measurement of the polarisation of single top quarks and antiquarks produced in the t-channel at √s = 13 TeV and bounds on the tWb dipole operator from the ATLAS experiment - Aad, Georges; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Dittmeier, Sebastian; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Journal of high energy physics, 2022)
A simultaneous measurement of the three components of the top-quark and top-antiquark polarisation vectors in t-channel single-top-quark production is presented. This analysis is based on data from proton-proton collisions at a centre-of-mass energy of 13 TeV corresponding to an integrated luminosity of 139 fb−1, collected with the ATLAS detector at the LHC.